Research Progress on the Regulation of Tumor Microenvironment in Immunotherapy - Ren, Jing; Xie, Wangge; Zhang, Hai (Journal of Contemporary Medical Practice, 2025)
The tumor microenvironment (TME) is an important component of cancer. Cancer cells can secrete a variety of cytokines, chemokines, and other factors, which can reprogram the surrounding cells and play a decisive role in tumor survival and progression. Immune cells are an important part of the tumor stroma and play a crucial role in anti-tumor immunity. An increasing amount of evidence shows that when innate immune cells (macrophages, dendritic cells, natural killer cells, and myeloid-derived suppressor cells) and adaptive immune cells (T cells and B cells) are present in the TME, they will promote tumor progression. Current research has identified new targets in the TME that can guide and improve the efficacy of various cancer therapies. This article reviews the latest understanding of the impact of immune cells, cancer-associated fibroblasts, hypoxia, etc. in the microenvironment on tumor immunotherapy, and discusses existing and potential strategies.